Do female representatives make a difference? : women full-time officials and trade union work - Heery, Edmund [Verfasser]; Kelly, John [Verfasser] (My University, 1988)
"The article presents information on the extent and distribution of women's employment in full-time officer posts within British trade unions, and on the priorities and objectives of those ten per cent of full-time bargainers in the British labour movement who are women. The main concern of the article is to establish whether the presence of women in representative positions in trade unions 'makes a difference'. It has been alleged by a number of commentators that British unions are neglectful of the separate interests of women workers in large part because women are absent from positions of power with the trade union hierarchy. The prescription for reform which usually follows such an analysis is that there should be a 'feminising' of trade union government and administration in order to facilitate the expression of women's concerns and needs within trade union activities. This article attempts to assess the validity of this belief by examining whether those women who have achieved positions of influence within unions are committed to using their position to redirect trade union work towards a fuller engagement with 'women's issues'. Specifically, it is concerned to establish whether women full-time officials are more likely than their male counterparts to give high priority to women's needs in collective bargaining and to the recruitment and organisation of women workers." (author's abtract) ((en)) Die empirische Studie untersucht die Stellung von Frauen in Funktionärspositionen der britischen Gewerkschaften. Dabei wird der Frage nachgegangen, inwieweit Frauen überhaupt solche Positionen erreichen können. Hauptaugenmerk der Untersuchung liegt auf dem Einfluss, den Gewerkschaftsfunktionärinnen auf frauenpolitische Entscheidungen in Tarifverhandlungen ausüben können. (IAB)
Machen weibliche Repräsentanten einen Unterschied. Weibliche Funktionäre und Gewerkschaftsarbeit
Keywords: S 3.5.4.1 Gewerkschaften; P 1.3 Frauen; Gewerkschaft; Frauen in Einzelberufen; Frauenarbeit; Berufsproblem; Gewerkschaftsarbeit; Gewerkschaftspolitik; Frauenpolitik; Tarifverhandlungen; Quantitative Angaben